Perancangan Sistem Informasi Arsip Kontrak Vendor Pada Departemen Pengadaan Jasa PT. Pupuk Sriwidjaja Palembang - Dhike Fidora; M. Syendi Apriko (CV. Shofanah Media Berkah, 2025)
Vendor contract archive management is an important aspect in supporting the smooth administration process in the Procurement Department of PT Pupuk Sriwidjaja Palembang. However, based on observations, archiving is still done manually, namely storing documents physically and recording data using basic spreadsheets. This situation causes several problems such as the length of time to search for documents, potential damage to archives, duplicate data, and challenges in maintaining the validity of agreements. To solve these problems, this study aims to design a web-based information system for agreement archives that can facilitate the storage, search, and management of agreement documents in a more systematic and integrated manner. The method applied in the development is Waterfall, which includes the stages of needs analysis, system design using UML, implementation with PHP and MySQL, and system testing through black-box testing. The results of the system design indicate that the developed information can accelerate document searches, reduce the risk of archive loss, and improve employee work efficiency in managing vendor contracts. Thus, this information system contributes to supporting digital transformation and more efficient administrative management. Information Systems, Contract Archives, Vendors, Service Procurement, Waterfall.